A Scoping Review of The Practicality of Participatory Budgeting in Rural Tanzania - Manara, Kenny (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
The current framework of participatory budgeting (PB) in Tanzania refers to the Opportunities and Obstacles to Development (O&OD) methodology. However, this policy tool seems to pay little attention to the rural-urban dichotomy, thus raising questions regarding its practicality in marginalized, rural areas. This article synthesized evidence based on the practicality of PB under the O&OD methodology in rural Tanzania to provide insights for decision-makers and practitioners at relevant levels of government. Employing a scoping study approach, the included publications consisted of policy studies (n = 6), academic papers (n = 8), and journal articles (n = 7), all of which covered rural district councils (n = 21). Research designs, analyses, and results of these included publications were examined. The synthesized evidence suggests that PB is context-sensitive and may not be applicable in rural Tanzania due to costs of participation, unconducive political culture, limited fiscal autonomy, and knowledge inclusiveness trade-off. Overall, the evidence from practicality categories indicates that PB is an induced bottom-up process, which may require robust facilitation by civil society to be practical in rural areas. This article has policy implications for the achievement of Sustainable Development Goal (SDG) 16, which promotes inclusive societies for sustainable development and access to justice for all through local governments.